2013
DOI: 10.3390/metabo3020204
|View full text |Cite
|
Sign up to set email alerts
|

NMR-Based Milk Metabolomics

Abstract: Milk is a key component in infant nutrition worldwide and, in the Western parts of the world, also in adult nutrition. Milk of bovine origin is both consumed fresh and processed into a variety of dairy products including cheese, fermented milk products, and infant formula. The nutritional quality and processing capabilities of bovine milk is closely associated to milk composition. Metabolomics is ideal in the study of the low-molecular-weight compounds in milk, and this review focuses on the recent nuclear mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(129 citation statements)
references
References 76 publications
(115 reference statements)
4
111
0
2
Order By: Relevance
“…The proton NMR spectra were phase and baseline corrected manually using Topspin 2.1 (Bruker Biospin). The NMR signals were assigned in accordance with existing literature (Sundekilde et al, 2013a), spike-in experiments, 2-dimensional NMR spectroscopy, and the Human Metabolome Database (Wishart et al, 2009).…”
Section: Nmr Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The proton NMR spectra were phase and baseline corrected manually using Topspin 2.1 (Bruker Biospin). The NMR signals were assigned in accordance with existing literature (Sundekilde et al, 2013a), spike-in experiments, 2-dimensional NMR spectroscopy, and the Human Metabolome Database (Wishart et al, 2009).…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…In Denmark and Sweden, respectively, 47 and 26% of total milk production is used for cheese production (Landrug and Fødevarer, 2013;LRF Dairy Sweden, 2014), which highlights the importance of a high technological milk quality. However, despite this, few studies have investigated the link between the technological properties of milk and its minor compounds composition (Sundekilde et al, 2013a). We have previously reported that NC or poorly coagulating milk samples were correlated to concentrations of choline, carnitine, lactose, and citrate, as elucidated by nuclear magnetic resonance (NMR) spectroscopy and multivariate data analysis (Sundekilde et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…One-dimensional high-resolution ¹H-NMR spectroscopy is the most widely used NMR approach in BM metabolomics (Sundekilde et al, 2013). Metabolite profiling using ¹H-NMR involves detection of chemically distinct hydrogen nucleus in each metabolite in a biological fluid, such as BM, that exhibits a NMR signal at a characteristic resonance frequency, which is measured as a chemical shift to a standard compound.…”
Section: Breastmilk Metabolomic Data Analysismentioning
confidence: 99%
“…Bucketing was performed within 10.00-0.5 ppm region, excluding the signal of the residual non-deuterated chloroform and its carbon satellites (7.6-6.9 ppm); total sum normalization was applied to minimize small differences due to total olive oil concentration and/or acquisition conditions among samples. The Pareto scaling method (performed by dividing the mean-centered data by the square root of the standard deviation) was then applied to the variables [29]. The data table generated by all aligned buckets row-reduced spectra was used for multivariate data analysis.…”
Section: H-nmr Spectra Pre-processing and Multivariate Statistical mentioning
confidence: 99%